Attack on synchronized artificial neural networks, forming a common secret by deferred search - V. F. Golikov; A. Y. Ksenevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The application of synchronized artificial neural networks for generation of a common cryptographic key and an attack by deferred search on these networks with the purpose of obtaining this key are considered.